5-Star Luxury Hotels’ Instagram Performance as a Digital Marketing Strategy during the Travelling Restriction - Desi Andriany; Ni Gusti Nyoman Suci Murni; Ni Nyoman Triyuni; Ni Made Sudarmini; Raden Ayu Trisnayoni (Catuspata Press, 2022)
Purpose: This study aims to enhance knowledge and improvement in online digital marketing, especially to increase domestic customers at 5-star luxury hotels in Nusa Dua, Bali, Indonesia. Research methods: Qualitative descriptive analysis technique is used to explain the development of digital marketing function towards tourism business. The object study is 5-star luxury hotels in Nusa Dua. Findings: Instagram performance during travel restriction and review in 4Ps marketing mix; product, price, place, and promotion. A strategy to increase and promote activities to meet customer needs in various occasion. Implication: Instagram has significant role in selling and promoting every brand of 5-star luxury hotels in Nusa Dua and its significant improvement following the updated technology progress and customer demand.